(untitled) (Informatica, 2014)
In this paper, a tiny low-power wireless sensor network (WSN) node based on msp430 microcontroller is introduced. The node should be serving the needs of a special WSN used for traffic monitoring, or more precisely for the indication of vehicle’s presence. The single vehicle detection is based on the utilization of magnetometer sensor, where the change of Earth’s magnetic field, caused by the movement of passing vehicle, is measured. Communication subsystem of the node is based on the low-power sub-GHz transceiver cc1101 implemented together with the special, energy-efficient communication protocol in 868 MHz ISM band. In line with low-power architecture, environment friendly power consumption of the node was reached. It is equal on average to 300uA, when transmitting period is 1s and magnetometer data collection rate is equal to 20Hz.